1993
DOI: 10.1016/0378-1097(93)90561-f
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of transferrin-bound iron by Listeria monocytogenes

Abstract: It has been demonstrated that under iron-restricted conditions, Listeria monocytogenes can utilize iron-loaded transferrin (Tf) from a range of species as its sole source of iron for growth. Human transferrin conjugated to horseradish-peroxidase (HRP-Tf) bound directly to whole cells of L. monocytogenes. This binding was blocked by apotransferrin indicating that the receptor can bind transferrin in either the iron-bound or iron-free form. Transferrin-binding was not host specific because both bovine and equine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Another system involves an extracellular ferric iron reductase, which uses as a substrate naturally occurring iron-loaded catecholamines and siderophores (2,21,111,112,133). The third system may involve a bacterial cell surface-located transferrinbinding protein (263), although the existence of such a mechanism has been questioned (43). No experimental evidence is currently available on the contribution of these iron uptake systems to the pathogenesis of L. monocytogenes infection.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…Another system involves an extracellular ferric iron reductase, which uses as a substrate naturally occurring iron-loaded catecholamines and siderophores (2,21,111,112,133). The third system may involve a bacterial cell surface-located transferrinbinding protein (263), although the existence of such a mechanism has been questioned (43). No experimental evidence is currently available on the contribution of these iron uptake systems to the pathogenesis of L. monocytogenes infection.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…Following infection, the mammalian host has several strategies to defend itself against invading microbes. One of these is to decrease the amount of available iron by binding free extracellular iron to iron-binding proteins such as transferrin and lactoferrin (Hartford et al, 1993). Iron is essential for most bacterial species, as it functions as a co-factor in different proteins, is involved in various cellular functions, and is a major environmental stimulus capable of regulating virulence gene expression in many bacterial pathogens (Adams et al, bind iron (Bozzi et al, 1997;Grant et al, 1998;Ilari et al, 2000;Tonello et al, 1999;Yamamoto et al, 2002;Zhao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Streptococcus pneumoniae, no siderophore synthesis has been detected in L. monocytogenes, and whole-genome sequence data of L. monocytogenes indicate that such genes are absent in this bacterium (Cowart & Foster, 1985;Tai et al, 1993;Glaser et al, 2001). It has been reported that L. monocytogenes can utilize transferrin, ferritin, lactoferrin, haemin, catecholamine, and siderophores produced by other bacteria in the environment, as sources of iron (Hartford et al, 1993;Jin et al, 2006; Mikael et al, 2002; Newton et al, 2005;Simon et al, 1995). Additionally, extracellular iron reductase activity has also been reported in this bacterium (Barchini & Cowart, 1996;Coulanges et al, 1997Coulanges et al, , 1998Cowart & Foster, 1985;Deneer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%